Mitoxantrone in combination with clofarabine (MITCL) in children, adolescents and young adults with relapsed/refractory acute leukaemia: final results of a phase I/II trialResearch in context - Jessica Hochberg; Javier Oesterheld; Aliza Gardenswartz; Allyson Flower; Liana Klejmont; Jackie Basso; Qiuhu Shi; Lauren Harrison; Michael J. Borowitz; Michael R. Loken; Mitchell S. Cairo (EClinicalMedicine)
Summary: Background: Children with relapsed/refractory acute leukaemias have lower response rates to reinduction and decreased overall survival. Mitoxantrone and clofarabine both have proven efficacy in acute leukaemia. We present our final results utilising this novel reinduction platform as a bridge to haematopoietic stem cell transplantation (HSCT) in children with high-risk pediatric leukaemias. Methods: From 2013 to 2021, patients 0–30.99 yr old with acute lymphoblastic leukaemia (ALL) or acute myelogenous leukaemia (AML) with relapse/refractory disease were given 1 to 3 cycles of clofarabine (escalating doses 20, 30, 35 and 40 mg/m2/day to establish the maximal tolerated dose [MTD]) days 1–5, in combination with mitoxantrone 12 mg/m2/day on days 3–6. The primary objective was to determine the maximal tolerated dose (MTD) or maximal acceptable dose of clofarabine in combination with mitoxantrone 12 mg/m2/day. The key secondary objective was to determine the overall response rate of the combination of mitoxantrone and clofarabine. The protocol was registered with clinicaltrials.gov (NCT01842672). Findings: Forty patients enrolled (18 phase I, 22 phase II) with median age 13 yrs (8 months–23 yrs). Demographics: 22 ALL (10 = induction failure [IF]/minimal residual disease [MRD], 9 = Relapse 1, 3 = Relapse 2), 17 AML (9 = IF/MRD, 6 = Relapse 1, 2 = Relapse 2). During phase I, there were 2 dose-limiting toxicities (DLTs) at dose level 4 requiring de-escalation to dose level 3. The phase I MTD was established at 35 mg/m2/dose clofarabine and continued in phase II. One patient with Burkitt Lymphoma was not included in this efficacy analysis. Thirty-three of 39 (85%) leukaemia patients achieved a complete response (CR). Of these, 88% achieved MRD negativity. Thirty-two of 33 patients went on to allogeneic HSCT. The event free survival/overall survival (EFS/OS) at 1 year was 74% for the entire cohort and 85% for responding/bridging patients at a median follow-up time of >75 months (range 30–120). Interpretation: The MTD of clofarabine in combination with mitoxantrone reinduction therapy was 35 mg/m2/dose x 5 days and was safe, well-tolerated and resulted in an 85% CR rate with 88% MRD negativity and, following HSCT, a 1 yr EFS/OS of 85%. Funding: Pediatric Cancer Research Foundation, Pediatric Cancer Foundation, Children's Cancer Fund, St. Baldrick's Foundation, Carolinas Healthcare, and NCCF subcontract #16252.